ARTISIPASI PEREMPUAN DALAM PERUMUSAN FATWA KEAGAMAAN DI INDONESIA (Studi Kasus pada Komisi Fatwa MUI, Majlis Tarjih dan Tajdid Muhammadiyah dan Lajnah Bahtsul Masa'il NU): WOMEN'S PARTICIPATION IN THE FORMULATION OF RELIGIOUS FATWAS IN Indonesia (Case Studies on the MUI Fatwa Commission, the Tarjih and Tajdid Council of Muhammadiyah, and the Bahtsul Masa'il Committee of NU - Fathiyaturrahmah (An-Nisa’ Journal of Gender Studies, 2012)
The phenomenon of women's marginalization in the public arena does not only occur in the realm of politics, but also extends to the interpretation of religious texts. Islamic jurisprudence products, which are summarized in the yellow book treasury, have become a discourse that can only be claimed as belonging to men. This reality is then perpetuated by a system of scientific transmission that favors men. The lack of female involvement in the process of shaping fiqh discourse as described above has continued into the contemporary era. This can be seen, among other things, in the low level of female participation in the formulation of religious fatwas in authoritative institutions such as the MUI Fatwa Commission, the Muhammadiyah Tarjih Council Muhammadiyah, and the NU's Lajnah Bahtsul Masa'il. Fenomena marginalisasi perempuan dalam arena publik tidak hanya terjadi dalam ranah politik semata, tetapi juga merambah pada wilayah penafsiran teks-teks agama. Produkproduk keilmuan fiqih Islam, yang terangkum dalam khazanah kitab kuning, menjadi diskursus yang hanya boleh diklaim sebagai milik kaum laki-laki. Realitas tersebut kemudian dilanggengkan oleh sistem transmisi keilmuan yang berpihak kepada laki-laki. Langkanya keterlibatan perempuan dalam proses pembentukan wacana fiqih seperti di atas ternyata juga berlanjut hingga zaman kontemporer. Hal ini antara lain dapat dilihat dalam rendahnya partisipasi perempuan dalam formulasi fatwa-fatwa keagamaan di lembaga-lembaga yang dipandang otoritatif seperti Komisi Fatwa MUI, Majlis Tarjih Muhammadiyah, Lajnah Bahtsul Masa'il NU.